Towards development of sustainable design in Malaysian university campus: A preliminary framework for Universiti Utara Malaysia - Abdul Nifa, Faizatul Akmar; Mohd Nawi, Mohd Nasrun; Osman, Wan Nadzri; Abdul Rahim, Syukran (Penerbit UTM Press, 2015)
This paper highlights the framework derived from a research in developing a framework for Development and Maintenance Department (JPP UUM) which employs sustainable design within the development of Universiti Utara Malaysia (UUM) campus.In realizing the aim of implementing sustainability, this paper also showcases Integrated Project Delivery (IPD) method as the potential mechanism in enabling sustainable design in planning for campus development.Through a number of semi-structured interviews, a framework for integrated project delivery is derived from themes identified in the insights of various functions within JPP UUM.It is concluded that a more proactive approach from the campus management is needed to ensure all components in the framework to come together for sustainable efforts to succeed.